1994
DOI: 10.1161/01.atv.14.10.1529
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine attenuates platelet reactivity in hypercholesterolemic rabbits.

Abstract: Platelets are capable of producing nitric oxide (NO) through the L-arginine-NO synthase pathway. Acute exposure to supraphysiological concentrations of L-arginine in vitro increases the production of NO by platelets and is associated with an increase in platelet cyclic GMP (cGMP) levels and a reduction in platelet aggregation. The purpose of this study was to determine if chronic oral administration of L-arginine decreases platelet aggregation in hypercholesterolemic animals and to determine if this effect is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 41 publications
1
58
0
2
Order By: Relevance
“…[61][62][63][64] Incubation of platelets with L-arginine at concentrations estimated to be produced in vivo in the present study resulted in inhibition of whole blood platelet aggregation to the same extent as during intra-arterial infusion of L-arginine, suggesting that the effect of L-arginine is exerted directly on platelets in the lumen and not via stimulation of the endothelial NO pathway. This direct platelet inhibitory effect of L-arginine appears to be secondary to increased platelet NO activity, 14,65 and human studies that used oral supplementation of L-arginine, which increases plasma L-arginine levels by up to 2-fold, have also shown inhibition of platelet aggregation in normal individuals and patients with hypercholesterolemia.…”
Section: L-argininementioning
confidence: 98%
“…[61][62][63][64] Incubation of platelets with L-arginine at concentrations estimated to be produced in vivo in the present study resulted in inhibition of whole blood platelet aggregation to the same extent as during intra-arterial infusion of L-arginine, suggesting that the effect of L-arginine is exerted directly on platelets in the lumen and not via stimulation of the endothelial NO pathway. This direct platelet inhibitory effect of L-arginine appears to be secondary to increased platelet NO activity, 14,65 and human studies that used oral supplementation of L-arginine, which increases plasma L-arginine levels by up to 2-fold, have also shown inhibition of platelet aggregation in normal individuals and patients with hypercholesterolemia.…”
Section: L-argininementioning
confidence: 98%
“…In HC rabbits, long-term oral administration of L-arginine restores endothelial elaboration of NO, reduces endothelial adhesiveness for monocytes, inhibits platelet aggregation, retards atherogenesis, and even induces regression of preexisting lesions. 12,13,[15][16][17][18][19][20][21][22]44 By contrast, longterm antagonism of NO synthase accelerates atherogenesis in animal models. 13,14,16,45 Recently, it has been observed that ADMA levels are correlated with the severity of disease in patients with peripheral arterial disease.…”
Section: Böger Et Almentioning
confidence: 99%
“…It is well known that L-arginine supplementation enhances the synthesis of endothelium-derived NO, 30 restores endothelial vasodilator function, [32][33][34] inhibits platelet aggregation 35,36 and cell adhesion, 20,[37][38][39][40] and attenuates atherosclerosis [41][42][43][44][45] in hypercholesterolemic animals and in humans. It is possible that L-arginine exerts these beneficial effects by reversing the action of the competitive inhibition by ADMA.…”
mentioning
confidence: 99%